Investigations of structural vibrations problems of high performance machines - Rusinski Eugeniusz; Moczko Przemyslaw; Odyjas Piotr; Pietrusiak Damian (FME Transactions, 2013)
High performance machines are prone to presence of different types of dynamic loads, which can lead to vibrations of the entire structures or their local parts. In the paper examples of identifications of vibration problems of High Performance Machines are shown. Investigations base on experimental methods and numerical simulations. In addition, the methods of preventing vibration of the investigated objects such as bucket wheel excavators, roller mills, crushers, load carrying structures are presented.